From the USSR to Che: The terror of the "ghost of communism" in Colombia: El terror al “fantasma del comunismo” en Colombia (2022)
This writing is a reflection on the situation of fear of communism in Colombia, based on a reflection on the history of the Union of Soviet Socialist Republics (USSR) and the influence that Stalinism had as a policy contradictory to Marxism, for On the other hand, it reflects on the guerrilla war proposed by Ernesto "Che" Guevara de la Serna for the establishment of a socialist government, in order to analyze the mistakes made by the Revolutionary Armed Forces of Colombia, the Popular Army (FARC-EP).